2013
DOI: 10.1111/j.1365-2125.2012.04401.x
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of glucose lowering drugs in the United Kingdom in the last decade: a focus on the effects of safety warnings about rosiglitazone

Abstract: Aim In the last decade, new glucose lowering drugs (GLDs) have been launched, and also several warnings regarding their safety. The cardiovascular safety of thiazolidinediones (TZD) has been questioned. We analyzed the prescription pattern of GLDs from 2000 to November 2009 in the United Kingdom (UK) using the THIN database with special focus on the effects of the safety warnings about rosiglitazone issued in May 2007 and January 2008. Methods Annual prevalence and incidence of GLD prescriptions were measured.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 22 publications
10
33
0
1
Order By: Relevance
“…Data from The Health Improvement Network (THIN) primary care database in the UK suggest that these drugs accounted for over 3 prescriptions per 1000 personyears, with rosiglitazone making more than double the contribution of pioglitazone [36]. Within 18 months of publication of the meta-analysis questioning the cardiovascular safety of rosiglitazone [18], the number of rosiglitazone prescriptions halved and the number of pioglitazone prescriptions doubled [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from The Health Improvement Network (THIN) primary care database in the UK suggest that these drugs accounted for over 3 prescriptions per 1000 personyears, with rosiglitazone making more than double the contribution of pioglitazone [36]. Within 18 months of publication of the meta-analysis questioning the cardiovascular safety of rosiglitazone [18], the number of rosiglitazone prescriptions halved and the number of pioglitazone prescriptions doubled [36].…”
Section: Discussionmentioning
confidence: 99%
“…Data from The Health Improvement Network (THIN) primary care database in the UK suggest that these drugs accounted for over 3 prescriptions per 1000 personyears, with rosiglitazone making more than double the contribution of pioglitazone [36]. Within 18 months of publication of the meta-analysis questioning the cardiovascular safety of rosiglitazone [18], the number of rosiglitazone prescriptions halved and the number of pioglitazone prescriptions doubled [36]. Overall, while the TZD prescription rate is lower now than in 2007, currently, 10% of all prescriptions for patients with type 2 diabetes in the THIN cohort are prescribed a TZD [37] and pioglitazone retains its position at the frontline of diabetes management [19,37].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the improvements observed in AIx in the current study (which suggest an improvement in endothelial function) may also occur as a result of exercise-induced activation of PPARγ. Thus, while due to an association with increased risk of death from CV causes [51], the prescription of RSG has fallen dramatically in recent years [52], exercise may provide a safe alternative to RSG as a method of inducing beneficial PPARγ-dependent effects [36,37]. Therefore, with regard to the current study's findings, we propose that an exerciseinduced activation of the nuclear receptor PPARγ may cause the observed down-regulation in the expression of the elastin-degrading gene MMP-9 (and also possibly improve endothelial function), which in turn may ameliorate physical inactivity-related vascular remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…According to the statement of the American Diabetes Association and European Association for the Study of Diabetes guidelines also endorses metformin is the first-line drug for Type 2 diabetes patients and has the lowest risk of hypoglycemia, it does not cause weight gain and weight loss, has the beneficial effect of lowering the lipid levels and available at a low cost [16,17]. The study conducted by different groups reported that an increase in the use of metformin and decrease in the use of sulfonylureas [18][19][20][21]. The addon therapy of sulfonylurea to metformin is the common procedure after the metformin fails to control glycemic levels, sulfonylureas have been associated with hypoglycemia, sometimes need of hospitalizations, particularly in elderly patients [22].…”
Section: Geetha and Shanmugasundharammentioning
confidence: 99%